PRODUKTIVITAS EMPAT JENIS RUMPUT PADA BERBAGAI TINGKAT PEMUPUKAN NPK - Junaidi, Muhammad (Fakultas Peternakan Universitas Papua, 2012)
This research is done at Taman Ternak FPPK UNIPA Manokwari that attributed to known productivity four grass kinds in fertilizing level NPK. This research uses experiment method with random group plan with factorial pattern. The treatment consists of two factors that is four grass kinds (Pennisetum purpuroides, penisetum purpureum, Sorghum Sp. Panicum maximum) and three fertilizing doses with five group, so that effort unit totals as much as 60. Defoliasi is done after aged grass 45 days. Fresh production of Pennisetum purpurhoides differ very significant than Pennisetum purpureum, Sorghum Sp. and Panicum maximum where does average successive highest fresh production Pennisetum purpurhoides that is 89696 kg/ha/defoliasi, sorghum Sp. that is 30853 kg/ha/defoliasi, Pennisetum purpureum that is 26416 kg/ha/defoliasi and Panicum maximum that is 23570 kg/ha/defoliasi. Fresh production with dose urea 100 gr + tsp 50 gr + kcl 50 gr and urea 200 gr + tsp 100 gr + kcl 100 gr differ significant than without fertilizing, where does average successive highest fresh production dose urea 200 gr + tsp 100 gr + kcl 100 gr that is 45194 kg/ha/defoliasi, dose urea 100 gr + tsp 50 gr + kcl 50 gr that is 45046 kg/ha/defoliasi and without fertilizing that is 37614 kg/ha/defoliasi. Dry matter production of Pennisetum purpuroides differ very significant than Pennisetum purpureum, Sorghum Sp. and Panicum maximum where does average successive highest dry matter production of Pennisetum purpuroides that is 13026 kg/ha/defoliasi, Sorghum Sp. that is 6555 kg/ha/defoliasi, Pennisetum purpureum that is 6243 kg/ha/defoliasi and Panicum maximum that is 4723 kg/ha/defoliasi. Average successive highest dry matter production dose urea 100 gr + tsp 50 gr + kcl 50 gr that is 7845 kg/ha/defoliasi, dose urea 200 gr + tsp 100 gr + kcl 100 gr that is 7705 kg/ha/defoliasi and without fertilizing that is 7360 kg/ha/defoliasi.